Neurological examination of Pacific harbor seal (Phoca vitulina richardii) pups: development and assessment of a protocol - Thomson, Christine E.; Field, Cara L.; Whoriskey, Sophie T.; McClain, Abby M.; Duignan, Pádraig J.; Castellini, J. Margaret; Lian, Marianne; Kruse-Elliott, Kris T.; Dennison, Sophie; O’Hara, Todd M. (Frontiers in Veterinary Science, 2025)
Stranded Pacific harbor seal (HS, Phoca vitulina richardii) pups admitted to rehabilitation centers have a variety of health problems, including neurological disorders. However, the standard neurological examination protocol for land-based quadrupeds does not suit marine mammals such as seals. In this study we aimed to develop and establish a neurological examination protocol (NEx) for phocid seal pups undergoing rehabilitation. In two consecutive years, we assessed stranded HS pups (n = 45; males n = 21, females n = 24) in care at The Marine Mammal Center (TMMC), Sausalito, California. The draft protocol developed in year 1 was refined to yield 33 tests, including many tests from domestic small animal examination, as well as novel tests dictated by the animals’ functional anatomy. The latter included the sloping ramp to assess proprioception and motor function, the handstand (to assess neck reflexes), banana pose, and grasp reflex. A fish head was suspended above the subject to assess balance, strength, coordination, and cranial nerve function, including visual field. Specific tests were considered highly useful if they had a reliable outcome in ≥ 80% of cases. In some pups, temperament made it challenging to discern the outcomes of some tests. The reliability of the 33 tests was assessed during repeated examinations on 17 animals; 26/33 tests yielded a reliable response in ≥ 80% of the exams. Three pups (L, P, and N) with suspected neurological deficits were assessed using the protocol. The NEx accurately predicted the neuroanatomical lesion localization, as confirmed by imaging and/or necropsy results. The neurological examination protocol developed for HS pups takes 9–12 min to perform. Although this protocol was developed in HS pups, it should be adaptable for other phocids.